T cell depletion by exposure to Campath-1G in vitro prevents graft-versus-host disease. - Jacobs, P; Wood, L; Fullard, L; Waldmann, H; Hale, G (1994)
Campath-1G is an immunosuppressive monoclonal antibody directed against human lymphocytes. Its effectiveness in preventing graft-versus-host disease (GVHD) by simple opsonisation of bone marrow T-cells has been studied in 36 consecutive allografts: in 17 for leukaemia, one for essential thrombocytosis and four for myeloma this was the sole means of GVHD prophylaxis. A further eight patients with aplastic anaemia received 3 months post-transplantation cyclosporin A (CsA) for this purpose whereas in the ninth and tenth the preparative regimen has been modified with this immunosuppressive agent now discontinued. Nucleated cells were harvested and after quantitative recovery of the mononuclear population on the Cobe 2997 separator they were exposed to 20 mg Campath-1G for 30 min at room temperature and then infused. Following standard conditioning, which included total lymphoid irradiation, the median days to reach 0.5 and 1.0 x 10(9)/l neutrophils were respectively 18 (range 9-34) and 28 (range 10-59); to 25 and 100 x 10(9)/l platelets the corresponding times were 17 days (range 5-32 days) and 27 days (range 13-127 days). In all, the day 14 trephine biopsy showed engraftment. At median follow-up of 20 months (range 5-44 months) only one patient has developed possible grade I cutaneous GVHD that responded promptly to corticosteroids: no chronic GVHD or CMV pneumonitis has been encountered. Of those with haematological malignancy transplanted in remission only two with acute leukaemia have relapsed. In aplastic anaemia graft loss initially occurred but this has been overcome by adding Campath-1G in vivo and omitting CsA.(ABSTRACT TRUNCATED AT 250 WORDS)